EFFECTIVENESS OF MUNICIPAL POLICE UNIT’S STREET VENDOR CONTROLLING PROGRAM IN ANDIR DISTRICT, BANDUNG CITY - Buchari, Rd Ahmad; Andari, Rosita Novi (JBFEM, 2018)
The objective of the present research was to evaluate the effectiveness of the controlling program by municipal police unit (Satpol PP) on street vendors (PKLs) in Andir District of Bandung City. The research used a qualitative approach, data collection techniques of documentation, interview, and observation, and a qualitative-descriptive analysis. The research findings revealed that the controlling by Satpol PP has not been effective yet in achieving the goal of the controlling related to the policy on PKL arrangement and guidance as stipulated by Perda (regional statute) No. 4 of 2011 and Perwal (Mayor Decree) No. 888 of 2012 particularly for Andir District, i.e., zero growth (PKLs at red zones should be reduced to zero). There were still gap between the regulation of the allocation of PKLs zones and breaches against Perda.